Implementasi Peran Bidan Dalam Pemberian ASI Eksklusif Sesuai Permenkes no 28 Tahun 2017 Di Puskesmas Ngeltih Kota Kediri - Ellatyas Rahmawati (Smart Law Journal, 2024)
Breast milk is very important for your baby's development. The benefits of exclusive breastfeeding from 0 to 6 months of age play an important role in strengthening the baby's immune system and promoting the baby's brain and physical development. Midwives have the authority to facilitate or guide early breastfeeding and encourage exclusive breastfeeding, as stated in Regulation No. 28 of 2017 of the Ministry of Health on Licensing and Implementation of Practices. midwifery practice, Article 19, Paragraph 3(g), and child health services in Article 19, Paragraph 3. Research methods used Sociological law is used, which uses analysis to study the operation of law in society. The primary data source used was taken from interviews with midwives at Ngletih Health Center, Kediri town, while the secondary data used was from data and library documents, including primary legal documents, secondary legal documents, and non-legal documents suitable for discussion. . Research results were obtained through Regulation No. 28 dated 2-017 of the Ministry of Health on the recognition and implementation of midwifery practice. Article 19(g) and Article 20(3): Midwives have the right to guide early breastfeeding and encourage exclusive breastfeeding, as stated. Essential Neonatal Services has been implemented in Maternal and Child Health Services at Ngletih Community Health Centre, Kediri Town.